2018
DOI: 10.1002/admi.201801449
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Primal sp2 Defects at the Diamond Surface: Candidates for Electron Trapping and Noise Sources

Abstract: COMMUNICATION (1 of 8)Diamond materials are central to an increasing range of advanced technological demonstrations, from high power electronics to nanoscale quantum bioimaging with unprecedented sensitivity. [1] However, the full exploitation of diamond for these applications is often limited by the uncontrolled nature of the diamond material surface, which suffers from Fermi-level pinning and hosts a significant density of electromagnetic noise sources. [2] These issues occur despite the oxide-free and air-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
113
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(120 citation statements)
references
References 59 publications
7
113
0
Order By: Relevance
“…2d), and a reduction in the mean NV − depth from ≈ 23 nm to ≈ 19 nm. These trends are broadly consistent with direct measurements of D sd reported recently [26]. We note that another avenue to reduce D sd is by etching the diamond, as shown in the SI.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…2d), and a reduction in the mean NV − depth from ≈ 23 nm to ≈ 19 nm. These trends are broadly consistent with direct measurements of D sd reported recently [26]. We note that another avenue to reduce D sd is by etching the diamond, as shown in the SI.…”
supporting
confidence: 91%
“…To estimate E z , we first consider the case of commonly used oxygen-terminated diamond. It was recently found that such samples typically host surface defects that introduce an acceptor level into the band-gap, with densities (D sd ) as high as 1 nm −2 [26]. An example of a calculated electric field profile for this scenario (with parameters representative of our implanted samples) is plotted in Fig.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…This effect has been investigated previously by varying the surface chemistry of the diamond [38,39] and by electrostatic gating of NV centres [19,40,41]. Here, we suggest that an increasing gate potential populates an acceptor layer at the diamond surface [42], given the low carrier density within the implanted region, and hence increases the band bending across the NV-layer. As the band bending increases, the Fermi level falls below the NV − charge state at greater depths within the diamond.…”
Section: Pl Switching Effectmentioning
confidence: 51%